Effects of participatory forest management on livelihood assets in Gebradima forest, southwest Ethiopia. Issue 4 (2nd October 2017) - Tadesse, Solomon; Woldetsadik, Muluneh; Senbeta, Feyera
Abstract: This paper analyzes the effects of a five year participatory forest management (PFM) program on livelihood assets of the participants in Gebradima forest, southwest Ethiopia. A cross-sectional survey research design was employed to collect information from 322 randomly selected PFM participant and non-participants households in six rural kebeles. Descriptive statistics and independent t-test were used to analyze the data. Results showed that the overall value of livelihood assets was higher for PFM participants (0.76) than for non-participants (0.63). We found that there were statistically significant ( p  < 0.05) differences between the two studied groups on access to natural and social assets measured variables. Financial and human assets also showed a significant difference in terms of knowledge and skills gained and access to market. However, no significant variations were found in physical asset indicators between the two groups. Overall, this study showed that there was only a slight improvement in financial and human assets of participants, while natural and social assets showed a remarkable improvement. This research therefore suggests that further emphasis is needed to enhance the financial, physical and human capitals of the participants for sustainability of both livelihoods and forest resources.